The sisters brothers [large type] - deWitt, Patrick, 1975- (Thorndike Press large print basic, 2011)
Hermann Kermit Warm is going to die. The enigmatic and powerful man known only as the Commodore has ordered it, and his henchmen, Eli and Charlie Sisters, will make sure of it. Though Eli doesn't share his brother's appetite for whiskey and killing, he's never known anything else. But their prey isn't an easy mark, and on the road to Warm's gold claim outside Sacramento, Eli begins to question what he does - and for whom he does it.